Tumor Necrosis Factor Receptor Superfamily, Member 1B Haplotypes Increase or Decrease the Risk of Inflammatory Bowel Diseases in a New Zealand Caucasian Population - Lynnette R. Ferguson; Dug Yeo Han; Claudia Huebner; Ivonne Petermann; Murray L. Barclay; Richard B. Gearry; Alan McCulloch; Pieter S. Demmers (Gastroenterology Research and Practice)
Inflammatory bowel diseases (IBDs) comprising Crohn disease (CD) and ulcerative colitis (UC) are chronic inflammatory conditions with polygenic susceptibility. Interactions between TNF-alpha and TNF-alpha receptor play a fundamental role in inflammatory response. This study investigates the role that selected single nucleotide polymorphisms (SNPs) and haplotypes in the TNF-alpha receptor (TNSFRSF1B) gene play in the risk of IBD in a New Zealand Caucasian population. DNA samples from 388 CD, 405 UC, 27 indeterminate colitis patients, and 293 randomly selected controls, from Canterbury, New Zealand were screened for 3 common SNPs in TNSFRSF1B: rs1061622 (c.676T>C), rs1061624 (c.∗1663A>G), and rs3397 (c.∗1690T>C), using TaqMan technologies. Carrying the rs1061624 variant decreased the risk of UC in the left colon (OR 0.73, 95% CI=0.54–1.00) and of being a smoker at diagnosis (OR 0.62; 95% CI=0.40–0.96). Carrying the rs3397 variant decreased the risk of penetrating CD (OR 0.62, 95% CI=0.40–0.95). Three marker haplotype analyses revealed highly significant differences between CD patients and control subjects (χ2=29.9, df=7, P=.0001) and UC cases and controls (χ2=46.3, df=7, P<.0001). We conclude that carrying a 3-marker haplotype in the TNSFRSF1B gene may increase (e.g., haplotype of GGC was 2.9-fold more in the CD or UCpatients) or decrease (e.g., TGT was 0.47-fold less in UC patients) the risk of IBD in a New Zealand Caucasian population.